Komunikasi Antarbudaya Dalam Masyarakat Multikultur ( Studi Pada Masyarakat Etnik Jawa Dan Bali Di Desa Balirejo) - Ramdana Dhana; Jeanny Maria Fatimah; Muhammad Farid (KOMUNIDA : Media Komunikasi dan Dakwah, 2022)
Multicultural society as a supporter of an intercultural communication that makes Balirejo Village community relations continues to run harmoniously even though they live side by side with different cultures. This study aims to determine the process of intercultural communication in the transmigration area by the people of Balirejo Village, Angkona District, South Sulawesi Province. To reveal this phenomenon, the author uses qualitative research methods using the social interaction model to see human behavior and interactions that can be distinguished because they are displayed through the communication process. To get the data, the writer uses three data collection techniques, namely observation, in-depth interviews and documentation review. The results of this study found that there has been a reciprocal adaptation between Javanese and Balinese ethnicities as immigrants in East Luwu Regency and residing in Balirejo Village. The existence of mutual respect and respect between ethnic groups allows each of these ethnic groups to carry out their respective cultures. People from ethnic Javanese and Balinese during the dialogue can use Javanese, Balinese or Indonesian with a typical East Luwu dialect. So far the relationship between the two ethnic groups has been going on without any significant obstacles because each ethnic group has accepted each other as they are.